Ação tocolítica de 3,6-dimetil éter galetina, flavonóide isolado de Piptadenia stipulacea (Benth.) Ducke, envolve canais para potássio em útero de rata - Carreiro, Juliana da Nóbrega (2012)
The flavonoid 3,6-dimethyl ether galetin (FGAL) was isolated from aerial parts of Piptadenia stipulacea (Benth.) Ducke. In previous studies, Macêdo et al. (2011a) demonstrated that FGAL inhibited in a significant and concentration-dependent manner the phasic contractions induced by carbachol and oxytocin on rat uterus, in a higher potency to oxytocin. The aim of this study was to investigate the mechanism of tocolytic action of FGAL on rat uterus. Segments of rat uterus were suspended in organ bath and the isometric contractions were monitored. FGAL inhibited (pD 2 = 5.68 ± 0.06) oxytocin cumulative curves and these were shifted to the right, in a non parallel manner (slope = 3.59 ± 0.04), with Emax the reduction, suggesting a non-competitive antagonism. In relation to the tonic contractions, FGAL relaxed in a concentration-dependent and significant manner but not equipotent rat uterus pre-contracted both oxytocin (pD2 = 6.9 ± 0.1) and KCl (pD2 = 5.6 ± 0.06). How the opening channels for calcium-dependent voltage (CaV) is one of the common step to the signaling pathways of oxytocin and KCl to maintain the tonic phase of contraction, raised the hypothesis that FGAL could be acting by blocking the influx of Ca2+ through the CaV. Therefore, cumulative contractions were induced with CaCl2 in depolarizing medium nominally without Ca2+ in the presence and absence of several concentrations of FGAL. The flavonoid antagonized the contractions induced by CaCl2 evidenced by shift to the right of the control curve in a non parallel manner with reduction of Emax, suggesting that FGAL is blocking indirectly the CaV to promote tocolytic effect on rat uterus. The K+ channels play a key role in membrane potential regulation and CaV modulation. According to this premise, we decided to investigate the involvement of these channels in the tocolytic action of FGAL. The relaxing potency of FGAL (pD2 = 6.9 ± 0.1) were reduced approximately 20 folds in the presence of CsCl (pD2 = 5.6 ± 0.01), a non-selective K+ channels blocker, confirming K+ channels the participation to the relaxant effect of the flavonoid. To determinated which K+ channel(s) subtype(s) were involved, selective blockers of these channels were used. The relaxation curve induced by FGAL was shifted to right in the presence of 4-aminopyridine (pD2 = 5.4 ± 0.01), a selective blocker of voltage gated K+ channels (KV); of glibenclamide (pD2 = 5.3 ± 0.01), a selective blocker of ATP sensitive K+ channels (KATP); of apamin (6.3 ± 0.02), a selective blocker of small conductance calcium-activated K+ channels (SKCa) and tetraethylamonium (TEA+) 1 mM (pD2 = 5.0 ± 0.08), a big conductance calcium-activated K+ channels (BKCa), suggesting the involvement of these channels on tocolytic action mechanism of FGAL on rat uterus. The aminophylline, a non selective inhibitor of phosphodiesterases (PDE), did not potentialized (pD2 = 6.7 ± 0.03) the relaxation produced by FGAL on rat uterus, suggesting that the cyclic nucleotides pathway is not involved on relaxing effect induced by FGAL. Thus, we concluded that the relaxing action mechanism of FGAL in rat uterus involves positive regulation of K+ channels, that indirectly modulated the CaV, leading to a consequent reduction of [Ca2+]c and uterine smooth muscle relaxation.